2022
DOI: 10.3390/jcs6040103
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Local Design of Deep Water Composite Risers to Minimise Structural Weight

Abstract: Following the rising technological advancements on composite marine structures, there is a corresponding surge in the demand for its deployment as ocean engineering applications. The push for exploration activities in deep waters necessitates the need for composite marine structures to reduce structural payload and lessen weights/loads on platform decks. This gain is achieved by its high strength–stiffness modulus and light-in-weight attributes, enabling easier marine/offshore operations. Thus, the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Comparisons based on the mechanical, chemical and physical properties of composites against steel and wood have shown that composites to have excellent behaviour in coastal environments, as opposed to mild steel [295][296][297][298][299][300]. To evaluate the strength of marine risers, effective tension profiles are usually used [11,[24][25][26][27]98,[137][138][139][140][141][142][149][150][151][152][153]. Details of similar effective tension profiles on marine hose risers are available in earlier studies [48][49][50][51][52][53].…”
Section: Strength Behaviourmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparisons based on the mechanical, chemical and physical properties of composites against steel and wood have shown that composites to have excellent behaviour in coastal environments, as opposed to mild steel [295][296][297][298][299][300]. To evaluate the strength of marine risers, effective tension profiles are usually used [11,[24][25][26][27]98,[137][138][139][140][141][142][149][150][151][152][153]. Details of similar effective tension profiles on marine hose risers are available in earlier studies [48][49][50][51][52][53].…”
Section: Strength Behaviourmentioning
confidence: 99%
“…Presently, the scale tends to shift more towards small-scale methods. The tests conducted include failure tests, fatigue, collapse and burst pressures [148][149][150][151][152]. There are limitations to fullscale testing, as can be seen in the size of composite risers as shown in Figure 19.…”
Section: Experimental Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are supporting attachments for these offshore installations that are used for a variety of functions and in a variety of water depths and environments globally. These components included drilling/production marine risers [17][18][19][20][21][22][23], composite risers [24][25][26][27][28][29][30], mooring lines [31][32][33][34][35][36][37][38][39], and marine hoses [40][41][42][43][44][45][46][47][48][49]. Figure 1 depicts some offshore platform installations.…”
Section: Introductionmentioning
confidence: 99%